2013
DOI: 10.1080/01694243.2012.762326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Br gassing after Ar plasma treatment of polyolefins

Abstract: For simulation and acceleration of artificial polymer ageing, polyolefin foils were exposed to low-pressure Ar plasma. Plasma particle bombardment and irradiation induce C-C and C-H bond scissions by σ → σ ⁄ excitations on the surface and in near-surface layers. Consequently, radicals are generated. They react by recombination, cross-linking, metastable trapping of the radical site or formation of olefinic double bonds. The long-living and metastable trapped C-radicals as well as double bonds in polyolefins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These radicals, arising from plasma–surface interactions, can be advantageously exploited for the controlled grafting of a specific chemical group or molecule. , Preliminary knowledge of the surface free-radical density, as discussed in the preceding section, can serve as a guide to achieving higher grafting efficiencies. To preserve the maximum number of surface free radicals from postoxidation reactions, the functionalization step, similarly to radical labeling, should preferably take place under a vacuum without air exposure.…”
Section: Plasma-initiated Polymerizationmentioning
confidence: 91%
“…These radicals, arising from plasma–surface interactions, can be advantageously exploited for the controlled grafting of a specific chemical group or molecule. , Preliminary knowledge of the surface free-radical density, as discussed in the preceding section, can serve as a guide to achieving higher grafting efficiencies. To preserve the maximum number of surface free radicals from postoxidation reactions, the functionalization step, similarly to radical labeling, should preferably take place under a vacuum without air exposure.…”
Section: Plasma-initiated Polymerizationmentioning
confidence: 91%
“…Photon irradiation and reacting plasma species bombardment can lead to C-C bond scissions that abstract CH 2 from terminal bonds generating metastable C-radicals. This carbon radical can further on react with furfural forming 2-furylmethyl ketone [32]. Part of the reactions observed in the powdered coffee subjected to cold plasma was also observed in the treatment of ready-to-drink coffee subjected to plasma processing [33].…”
Section: Resultsmentioning
confidence: 89%
“…This derivatization is possible via a side reaction by H substitution; however, there should be no nitrogen-containing stabilizers on the plasma-modified surface. A similar reaction between Br 2 and argon plasma treated PP and PE samples was used for quantification of radicals and/or C=C double bonds formed after plasma impact by applying XPS and ATR-FTIR [71]. It was demonstrated that bromine reacts mainly with the radicals which are present in the majority on the plasma-treated top surface layers.…”
Section: Surface and Interface Characterization Of Plasma Treated Pol...mentioning
confidence: 99%